Quantitative Fluorescent in situ Hybridization Reveals Differential Transcription Profile Sharpening of Endocytic Proteins in Cochlear Hair Cells Upon Maturation - Huang, Guobin; Eckrich, Stephanie (Frontiers in Cellular Neuroscience, 2021)
The organ of Corti (OC) comprises two types of sensory cells: outer hair cells (OHCs) and inner hair cells (IHCs). While both are mechanotransducers, OHCs serve as cochlear amplifiers, whereas IHCs transform sound into transmitter release. Reliable sound encoding is ensured by indefatigable exocytosis of synaptic vesicles associated with efficient replenishment of the vesicle pool. Vesicle reformation requires retrieval of vesicle membrane from the hair cell’s membrane via endocytosis. So far, the protein machinery for endocytosis in pre-mature and terminally differentiated hair cells has only partially been deciphered. Here, we studied three endocytic proteins, dynamin-1, dynamin-3, and endophilin-A1, by assessing their transcription profiles in pre-mature and mature mouse OCs. State-of-the-art RNAscope® fluorescent in situ hybridization (FISH) of whole-mount OCs was used for quantification of target mRNAs on single-cell level. We found that pre-mature IHCs contained more mRNA transcripts of dnm1 (encoding dynamin-1) and sh3gl2 (endophilin-A1), but less of dnm3 (dynamin-3) than OHCs. These differential transcription profiles between OHCs and IHCs were sharpened upon maturation. It is noteworthy that low but heterogeneous signal numbers were found between individual negative controls, which highlights the importance of corresponding analyses in RNAscope® assays. Complementary immunolabeling revealed strong expression of dynamin-1 in the soma of mature IHCs, which was much weaker in pre-mature IHCs. By contrast, dynamin-3 was predominantly found in the soma and at the border of the cuticular plates of pre-mature and mature OHCs. In summary, using quantitative RNAscope® FISH and immunohistochemistry on whole-mount tissue of both pre-mature and mature OCs, we disclosed the cellular upregulation of endocytic proteins at the level of transcription/translation during terminal differentiation of the OC. Dynamin-1 and endophilin-A1 likely contribute to the strengthening of the endocytic machinery in IHCs after the onset of hearing, whereas expression of dynamin-3 at the cuticular plate of pre-mature and mature OHCs suggests its possible involvement in activity-independent apical endocytosis.